Development of Learning Media Flipbook Digital Japanese Culinary Material in the Asian Food as Literacy Course Digital - Amira Thifalli; Cucu Cahyana; Annis Kandriasari (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to develop digital learning media in the form of a flipbook containing Japanese cuisine materials for Culinary Education students and to assess its feasibility. The development process implemented the Research and Development (R&D) method with the 4D development model, which consists of four stages: Define, Design, Develop, and Disseminate. Data analysis in this development study took the form of qualitative description. The flipbook has been validated by experts in related fields, resulting in a feasibility percentage of 91% for the material aspect, 96% for the media aspect, and 95% for the language aspect, with all three aspects classified as highly feasible. The flipbook media then underwent a trial phase with Culinary Education students, resulting in an assessment percentage of 92% for the one-to-one test, 93% for the small group test, and 95% for the field test. The resulting data calculation of student response scores to the flipbook was 93.5%, classified as very strong and very positively accepted. Based on the results of the study, it can be conclusively stated that the development of digital flipbook learning media for Japanese cuisine materials is feasible for use and publication to the wider community.